Action and Conduct : Thomas Aquinas and the Theory of Action - Brock, Stephen Louis (Book collections on Project MUSE., 2021)
Stephen Brock examines the relation between conduct and physical action, or between the 'will' and the real events which it effects in the world, through the works of Thomas Aquinas. Few thinkers have devoted more attention to this topic than Thomas, who has influenced mainstream modern analytic philosophy through (among others) G. E. M. Anscombe, Anthony Kenny, Roderick Chisolm and the late Alan Donagan. Demonstrating an exhaustive knowledge of Thomas and of contemporary theories of action, Professor Brock provides a new interpretation of Thomas' thought on human action and exposes the incoherence of theories which place an exclusive emphasis on the morality of subjective intention.